Lexicographical and Translation Issues in the Inclusion of English - Mateo Martinez, José (HERMES - Journal of Language and Communication in Business, 2014)
This is a crossroads time for dictionaries in print in general and for bilingual dictionaries of Economics in print in particular. A time when the prevalence of information technologies supposedly makes access to specialized lexicographical information easier and faster. The present study first reviews briefly the current situation of bilingual dictionaries of Economics on paper and their viability in a near future. It then examines, with more detail, the specific lexicographical issue of incorporating (i.e. translating) English financial neonyms, which appear practically everyday in print and internet media, into English-Spanish/Spanish-English Dictionaries of Economics on paper, normally published in the lapse of years. This gap between the immediacy of the Internet and the delay of printing, seems to cause serious problems to bilingual lexicographers specialized in Economics especially when questionable translations of such neonyms are already circulating on the web. This, in addition to the ample presence of electronic glossaries and dictionaries, easily accessible by translators and professionals, but whose reliability, on the other hand, is not always guaranteed. Finally, a more active role is recommended to bilingual lexicographers in Economics by taking advantage of internet information media services and by joining efforts with finance experts and professionals.